THE MANDINKA BALAFON: An introduction with notation for teaching, by Lynne Jessup, illustrated by Mary McConnell, Xylo Publications, La Mesa, California, 1983. Including two cassettes, pp 191, photographs, music - Tracey, Andrew (International Library of African Music, 1987)
pages: 159-160
Keywords: African Music